Six new species of Miconia (Miconieae, Melastomataceae) from the Andes - Burke, Janelle M.; Michelangeli, Fabian A. (Phytotaxa, 2018)
The eastern slopes of the Andes harbor some of the greatest amount of biodiversity, much of which remains undescribed in the scientific literature. Here, we describe six new species of Miconia from the Andes, encompassing the southernmost extent of the mountain range from Peru to Bolivia. The new species include Miconia cernuiflora, Miconia cinnabarina, Miconia dimorphotheca, Miconia dulcis, Miconia farfanii, and Miconia paucartambensis. Each species is compared with similar species. For each species, we include a diagnostic illustration, conservation assessment and range map. The number of species described underscores the continued need for exploration and field studies, especially as many of these species have extremely restricted distributions.